Cities, transport and agglomeration: Addressing the urban mobility challenges in India. (17th July 2019) - Mishra, Alok Kumar
Abstract: Cities are the drivers of economic growth and structural transformation in developing countries. Transport makes or mars a city. It connects people to opportunity and business to prosperity. Urban transport acts as a catalyst of growth through direct, indirect and induced effects, including those linked to agglomeration and networking externalities. Yet policy makers and planners in developing countries like India continue to neglect the economics of urban public transport. Hardly has there been any attempt to study relationships between city externalities, spatial planning, public transport infrastructure, economic growth and value capture financing. This paper delves into these aspects and presents lessons from theory for the strategies of development and financing of urban public transport in India. It is focused on the implications of urban externalities for transit‐oriented development, transport land use integration, strategic densification of growth nodes and public transport financing based on a value creation, capture and recycling paradigm.